Peran Wartawan Dalam Perlindungan Hak Anak Perspektif Undang-Undang Pers - Dedi Sahputra (PERSPEKTIF, 2021)
In the mass media coverage of children in conflict with the law, children's rights must be protected. Therefore journalists in producing journalistic works and mass media that disseminate information about children in conflict with the law must keep the identity of the child, both the child as the perpetrator, the child as the victim, and the child as a witness, as well as all information related to the child. In the process of producing journalistic work, a press institution has a flow of copy process which is a mechanism to ensure the fulfillment of checks and balances on the information produced. In addition, there is also a right of reply mechanism in the mass media that regulates if violations occur in journalistic work as mandated in the Press Law and Journalistic Code of Ethics. This mechanism is regulated is nothing but to guarantee the freedom of the press in carrying out the functions of the press which is essential in the life of the nation and state. With this right of reply mechanism, the press that publishes journalistic works that violate the rights of children in conflict with the law, must still be responsible without having to involve aspects of criminal law in it.